THE IMPACT OF COVID ON TOURISM AT THE EUROPEAN UNION LEVEL AS AN ELEMENT OF FINANCIAL RISK - Larisa DIMA; Mihaela STANCIU; Aurelia BALAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Tourism holds significant importance due to its multifaceted nature, encompassing economic, social, cultural, educational, and political dimensions. It plays a vital role in supporting and boosting a country's economy, motivating those who have been traveling for a long time and are doing it more frequently. Globally, the COVID-19 pandemic's quick and widespread spread has had a big impact, particularly on the travel and tourist industry. People’s ability to travel plays a crucial role in the growth of this industry, which is why the strict measures implemented by authorities to curb the virus greatly hindered tourism’s progress. This article aimed to explore the impact of the COVID-19 global pandemic on the tourism industry, highlighting the importance and sensitivity of crisis situations in this sector. The research methodology involved analyzing internal and international databases, calculating, analyzing, and interpreting statistical indicators regarding tourism flow. The findings of this study indicate that, by 2023, tourism demand had reached nearly 96% of the levels observed in 2021-2022. This demonstrates a remarkable recovery for the EU overall, with certain countries, such as Belgium, Germany, France, Italy, and Ireland, even surpassing their pre-pandemic levels.